ORAL ADMINISTRATION OF RAW WHITE KIDNEY BEANS (PHASEOLUS VULGARIS L. VAR. BELDIA) INDUCES OVERGROWTH OF FECAL COLIFORMS AND LACTOBACILLI IN WISTAR RATS - Nciri, Nader; Shin, Taesub; Cho, Namjun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The comprehensive dynamics of fecal microbiota in response to the ingestion of toxic bean lectins or phytohemagglutinins has not been well studied. The study aimed at evaluating the gavage effects of a raw Beldia bean variety on food intake, growth performance, gastrointestinal organs, and fecal microflora in Wistar rats. Methods: Twenty young adult male rats were randomly allotted into two groups of 10 rats each: Control rats were gavaged with 300 mg of a rodent pellet flour suspension and experimental rats were orogastrically fed a dose of 300 mg Beldia bean flour suspension (BBFS). Individual food intake, body weight, and fecal score were taken daily. To assess the impact on the gut flora, fecal samples were collected every day for 10 days. All animals were sacrificed on day 10, to obtain blood and internal organs samples. Results: The results revealed that the gavage of a BBFS to rats had no marked influence on average daily of food intake and weight gain. No significant differences were found in the weights of the small intestine, spleen, liver, and thymus of rats given raw Beldia diet. The counts of coliforms and lactobacilli on pooled fecal specimens of BBFS-fed rats were increased significantly compared to controls. Conclusion: In summary, the exposure to raw Beldia beans altered the fecal microbiota, without adverse effects on animals.